Aristotle’s Attainable and Attributable Phronimos - Shane D. Drefcinski (Philosophies, 2025)
Unlike many philosophers in the last quarter of the 20th century, many current scholars of Aristotle are less critical of the doctrine of the reciprocity of the virtues. They recognize that the reciprocity of the virtues is grounded in Aristotle’s accounts of eudaimonia, moral virtue, and phronēsis. However, there remains a concern that if the phronimos must have all the moral virtues in addition to phronēsis, then the phronimos is, for actual humans, unattainable. In what follows, I will argue that Aristotle’s phronimos is intended to be attainable and attributable to actual humans. In Part 2 of the paper, I will set out some preliminary points about the “methodology” Aristotle employs in his ethics, with special attention to the need to reconcile as many of the phenomena as one can and the recognition of the inescapable imprecision of ethics. In Part 3 of the paper, I will discuss passages where Aristotle insists upon the attainability of both eudaimonia and the moral virtues. In Part 4, I will explore how moral virtue and phronēsis admit of degrees and that his distinction between heroic virtue and moral virtue supports the attainability and attributability of the latter. Finally, in Part 5, I will propose a plausible reading of the reciprocity of the virtues that supports the thesis that the phronimos is attainable.